Three Mediating Pathways of Anxiety and Security in the Relationship between Coping Style and Disordered Eating Behaviors among Chinese Female College Students - Wenyue Han; Zheng Zheng; Ning Zhang (Neural Plasticity)
Background. According to previous studies, eating disorders and disordered eating behaviors are associated with coping style, anxiety, and sense of security. However, the specific mechanism between them has not been elucidated. The purpose of this study was to explore whether anxiety and sense of security play mediating roles in coping style and disordered eating behaviors among Chinese female college students. Method. Six hundred and ninety-one female college students (mean age=19.36; SD=1.06) completed the Simple Coping Style Questionnaire, the Eating Disorder Inventory, the Security Questionnaire, the Hospital Anxiety and Depression Scale, and a brief demographic survey. The percentage bootstrap method of deviation correction was conducted to determine the mediating effect of anxiety and sense of security on coping style and disordered eating behaviors. Results. Coping style had direct and indirect effects on disordered eating behaviors. Anxiety and sense of security were not only independent mediators in the relationship between coping style and disordered eating behaviors but also chain mediators. Conclusions. The results of the current study provide preliminary evidence that preventive interventions targeting anxiety and sense of security may be feasible for young women who develop disordered eating behaviors due to stress in their lives.